The Entrepreneurial Student's Experience Journey Through Engineering Education - Fallast, Mario; Vorbach, Stefan (International Journal of Engineering Pedagogy (iJEP), 2019)
The goal of this paper is to present a new perspective on how to design entrepre-neurial education in a wider sense. By applying the method of “customer journey mapping”, which is widely used in the field of marketing, the perspective of the student (“customer”) is put into the centre of attention. It intends to raise aware-ness for a more holistic and customer-centric view of the entrepreneurship-related “customer experience”. The paper shows the limitations of existing tools and procedures and gives an outlook on possible tools to describe customer experience journey in entrepre-neurship education.